Virtuous circles between innovations, job quality and employment in Europe? Case study evidence from the manufacturing sector, private and public service sector (QuinnE, 2018)
"Advanced capitalist economies currently face ‘disruptive’ innovations that profoundly challenge existing market structures and business models. Most notably, a new generation of digital technologies and a more general trend towards the ‘digital economy’ are expected to revolutionise the production and consumption of goods and services across industries, such as through advanced robotics and the industrial internet in the manufacturing sector, or FinTechs in the banking and finance sector."